THE EFFECT OF SERVICE ENVIRONMENT ON CUSTOMER EMOTION AT SARINA COFFEE KAWANGKOAN HOUSE - Rumondor, Cornelia; Massie, James D. D.; Gunawan, Emilia (Universitas Sam Ratulangi, 2021)
In the current era of globalization, the business world is developing very rapidly, one of which is business in the culinary field. The number of businesses that have arisen resulted in an increase in the number of businesses of a similar nature causing increasingly fierce competition. In accordance with the problems and research questions, the objectives in this study can be detailed as follows (1) To analyze the influence of the store's physical environment on consumers' emotions at Sarina Kawangkoan Coffee House dan (2) To analyze the influence of the store's social environment on consumers' emotions at Sarina Kawangkoan Coffee House. This type of research is explanatory research. Explanation method is a research method that describes the two variables studied namely the independent variable and the dependent variable which then explains the relationship or influence of the two variables. The data analysis technique used in this research is multiple linear regression. The following are the conclusions obtained from the results of this study as follows: (1) Physical Environment has no significant effect on Customer Emotion at Rumah Kopi Sarina Kawangkoan, (2) Social Environment does not have a significant effect on Customer Emotion at Sarina Kawangkoan Coffee House, and (3) Physical Environment and Social Environment have a significant effect on Customer Emotion at Rumah Kopi Sarina Kawangkoan.Â Keywords: service environment, customer emotion